Field reports form for submitting seasonal observations of Iowa birds, Beth Proescholdt, fall 1992 - Proescholdt, Bethet al (1992)
Fall report of a Hawk watch conducted at Grammar Grove County Wildlife Area contributed by Beth Proescholdt. A total of 133 Hawks were seen during the time period from September 9 through November 21, 1992. The report also includes detailed descriptions for the Peregrine Falcon and Golden Eagle sightings. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1992. Plustek - flatbed